Fluconazole dosing in continuous veno-venous haemofiltration (CVVHF): need for a high daily dose of 800 mg - Bergner, Raoul; Hoffmann, Martin; Riedel, Klaus-Dieter; Mikus, Gerd; Henrich, Dirk Markus; Haefeli, Walter E.; Uppenkamp, Michael; Walter-Sack, Ingeborg (Nephrology, dialysis, transplantation, 2006)
Abstract. To cover intermediate sensitive Candida glabrata in ICU patients, fluconazole plasma peak levels at least in the range of 16-32 µg/ml appear necessary